The Impact of Contingent Convertible Bonds Issuance on Profitability in the European Banking Sector - Marudkar, Manas (2017)
Contingent Convertible Bonds (CoCos) are a form of hybrid debt securities that have been proposed as a way of enhancing stability in the banking sector. Given they mandatorily convert from debt to equity when the issuing bank is in need of recapitalization, they have been lauded for reducing the chances of financial turmoil and the subsequent wide-spread problems that come with bank failure. In this paper, I run a fixed effects regression model to determine the impact that issuing CoCo bonds has on the profitability of 200 of the largest banks in Europe across a six-year period from 2011-2016. My analysis shows that, after controlling for numerous internal and external factors, a statistically significant link is found between CoCo bonds and profitability, suggesting that they are beneficial not only from a regulatory standpoint but also from a performance perspective. I have broadened my research to look at the impact of CoCos on shareholders of banks, their risks and danger, and the way it has allowed banks to alter their capital structure and minimize their risk-exposure. I have drawn links between the work of others on CoCos and my own analysis. Further results indicate that the structure of CoCos is vitally important in determining their practicality, and they should be used in conjunction with other devices aimed at controlling for risk-shifting. This way, their social benefits are maximised and financial institutions cannot influence their characteristics in an unethical manner for their own private gains.